The standards of reporting randomized trials in pets (PetSORT): Methods and development processes - Ruple, Audrey; Sargeant, Jan M.; Selmic, Laura E.; O'Connor, Annette M. (Frontiers in Veterinary Science, 2023)
Background: Reporting of clinical trials conducted in client- and shelter-owned dog and cat populations is not optimal, which inhibits the ability to assess the reliability and validity of trial findings and precludes the ability to include some trials in evidence synthesis. Objective: To develop a reporting guideline for parallel group and crossover trials that addresses the unique features and reporting requirements for trials conducted in client- and shelter-owned dog and cat populations. Design: Consensus statement. Setting: Virtual. Participants: Fifty-six experts from North America, the United Kingdom, Europe, and Australia working in academia, government (research and regulatory agencies), industry, and clinical veterinary practice. Methods: A steering committee created a draft checklist for reporting criteria based upon the CONSORT statement and the CONSORT extensions for reporting of abstracts and crossover trials. Each item was presented to the expert participants and was modified and presented again until greater than 85% of participants were in agreement about the inclusion and wording of each item in the checklist. Results: The final PetSORT checklist consists of 25 main items with several sub-items. Most items were modifications of items contained in the CONSORT 2010 checklist or the CONSORT extension for crossover trials, but 1 sub-item pertaining to euthanasia was created de novo. Conclusion: The methods and processes used to develop this guideline represent a novel departure from those used to create other reporting guidelines, by using a virtual format. The use of the PetSORT statement should improve reporting of trials conducted in client- and shelter-owned dogs and cats and published in the veterinary research literature.